Hybrid Capture‐Based Comprehensive Genomic Profiling Identifies Lung Cancer Patients with Well‐Characterized Sensitizing Epidermal Growth Factor Receptor Point Mutations That Were Not Detected by Standard of Care Testing. (14th March 2018) - Suh, James H.; Schrock, Alexa B.; Johnson, Adrienne; Lipson, Doron; Gay, Laurie M.; Ramkissoon, Shakti; Vergilio, Jo‐Anne; Elvin, Julia A.; Shakir, Abdur; Ruehlman, Peter; Reckamp, Karen L.; Ou, Sai‐Hong Ignatius; et al.
Abstract : Background: In our recent study, of cases positive for epidermal growth factor receptor ( EGFR ) exon 19 deletions using comprehensive genomic profiling (CGP), 17/77 (22%) patients with prior standard of care (SOC) EGFR testing results available were previously negative for exon 19 deletion. Our aim was to compare the detection rates of CGP versus SOC testing for well‐characterized sensitizing EGFR point mutations (pm) in our 6, 832‐patient cohort. Materials and Methods: DNA was extracted from 40 microns of formalin‐fixed paraffin‐embedded sections from 6, 832 consecutive cases of non‐small cell lung cancer (NSCLC) of various histologies (2012–2015). CGP was performed using a hybrid capture, adaptor ligation‐based next‐generation sequencing assay to a mean coverage depth of 576×. Genomic alterations (pm, small indels, copy number changes and rearrangements) involving EGFR were recorded for each case and compared with prior testing results if available. Results: Overall, there were 482 instances of EGFR exon 21 L858R (359) and L861Q (20), exon 18 G719X (73) and exon 20 S768I (30) pm, of which 103 unique cases had prior EGFR testing results that were available for review. Of these 103 cases, CGP identified 22 patients (21%) with sensitizing EGFR pm that were not detected by SOC testing, including 9/75 (12%) patients with L858R, 4/7 (57%) patients with L861Q, 8/20 (40%) patients with G719X, and 4/7 (57%) patients with S768I pm (some patients had multiple EGFR pm). In cases with available clinical data, benefit from small molecule inhibitor therapy was observed. Conclusion: CGP, even when applied to low tumor purity clinical‐grade specimens, can detect well‐known EGFR pm in NSCLC patients that would otherwise not be detected by SOC testing. Taken together with EGFR exon 19 deletions, over 20% of patients who are positive for EGFR ‐activating mutations using CGP are previously negative by SOC EGFR mutation testing, suggesting that thousands of such patients per year in the U.S. alone could experience improved clinical outcomes when hybrid capture‐based CGP is used to inform therapeutic decisions. Implications for Practice: This study points out that genomic profiling, as based on hybrid capture next‐generation sequencing, can identify lung cancer patients with point mutation in epidermal growth factor receptor (EGFR) missed by standard molecular testing who can likely benefit from anti‐EGFR targeted therapy. Beyond the specific findings regarding false‐negative point mutation testing for EGFR, this study highlights the need for oncologists and pathologists to be cognizant of the performance characteristics of testing deployed and the importance of clinical intuition in questioning the results of laboratory testing. Abstract : This article compares the detection rates of comprehensive genomic profiling with standard of care testing for well‐characterized sensitizing EGFR point mutations.